2022
DOI: 10.3390/su142114438
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Sustainability in the Wake of the COVID-19 Global Pandemic: Does CSR Enhance Corporate Survival during a Market Crisis?

Abstract: This study investigates the effect of the COVID-19 global pandemic on the relationship between corporate social responsibility (CSR) and a firm’s sustainability. Prior studies on related topics empirically argue that CSR activities are highly likely to positively impact corporate sustainability. If this is true, firms that engage in CSR activities should demonstrate a higher degree of sustainability than their counterparts during the recent COVID-19 global pandemic. Using a sample of 390 Korean listed companie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 82 publications
2
2
0
Order By: Relevance
“…When ROA is used as the dependent variable, both the interaction terms turn out to be insignificant, demonstrating that the occurrence of COVID-19 has no impact on the ESGD–FP relation. Thus, for core disclosures our study reiterates the findings observed by Kim et al (2022), who observe an insignificant interaction effect. Regarding extended ESGD, our results support Beloskar and Rao (2023), Ding et al (2021) and Broadstock et al (2021), who observe a moderating effect of COVID-19.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…When ROA is used as the dependent variable, both the interaction terms turn out to be insignificant, demonstrating that the occurrence of COVID-19 has no impact on the ESGD–FP relation. Thus, for core disclosures our study reiterates the findings observed by Kim et al (2022), who observe an insignificant interaction effect. Regarding extended ESGD, our results support Beloskar and Rao (2023), Ding et al (2021) and Broadstock et al (2021), who observe a moderating effect of COVID-19.…”
Section: Resultssupporting
confidence: 90%
“…When ROA is used as the dependent variable, both the interaction terms turn out to be insignificant, demonstrating that the occurrence of COVID-19 has no impact on the ESGD-FP relation. Thus, for core disclosures our study reiterates the findings observed by Kim et al (2022), To address potential endogeneity concerns in the relationship between ESGD and FP, we conducted Durbin and Wu-Hausman tests. Both tests yielded insignificant chi-square values, indicating that the variables are exogenous, justifying the use of FE or RE models.…”
Section: Assessing Effect Of Core and Expanded Esgsupporting
confidence: 69%
See 1 more Smart Citation
“…According to earlier studies on similar subjects, CSR initiatives are likely to impact company sustainability positively. CSR has been shown to enhance corporate image and performance and can help businesses thrive sustainably, improve firm reputation, and achieve sustainable business performance (Feng et al, 2022;Kim et al, 2022;Qing & Jin, 2022).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Among recent studies, P. Peduzzi (Peduzzi, 2019) emphasizes that some aspects of disaster risk related to global environmental changes still don't have a clear meaning for the main stakeholders (governments, businesses, insurance companies or agencies). In turn, there are studies of the impact of the global pandemic examine the impact of the global COVID-19 pandemic on the relationship between corporate social responsibility (CSR) and firm sustainability (Kim et al, 2022). The authors argue that firms that are more active in CSR do not reduce the market risk associated with the global COVID-19 pandemic compared to their counterparts that are less active in CSR, that is, CSR doesn't provide a significant improving the company's market risks.…”
mentioning
confidence: 99%